لجان التدقيق ومدى تاثيرها على ممارسات التخطيط الضريبي: دراسة لعينة من الشركات الماليزية - كليبات, محمد أنيس; بلوم, نذير (جامعة الوادي - University of Eloued, 2023)
The study aimed to identify audit committees as a modern method of governance mechanisms, while measuring their impact on tax planning practices for a sample of seven companies listed on the Malaysia Stock Exchange during the period 2008-2017 (70 observations), using Panel Data models .The study concluded that the Malaysian companies under study focus on external consulting and expertise provided by major auditing firms (BIG4) in reducing their effective tax rates by up to 29%, which makes them bear effective taxes estimated at 0.005. Therefore, the audit committees have no impact on corporate tax planning practices
Audit committees and their impact on tax planning practices: a study of a sample of Malaysian companies
مقال
Keywords: حوكمة الشركات ; تخطيط ضريبي ; شركات التدقيق والمراجعة الكبرى ; لجان التدقيق ; معدلات ضرائب فعالة; Corporate governance, tax planning, major audit firms, audit committees, effective tax rates